Dante’s Plot on Francesco and Paolo in Spanish Literature of the 15th–17th Centuries - Irina V. Ershova (Studia Litterarum, 2022)
The article discusses the reception of the Divine Comedy (La Divina Commedia) by Dante Alighieri and, in particular, of Canto 5 of the Inferno and its central episode — Dante’s encounter with Francesca and Paolo, in Spanish literature of the 15th–17th centuries. It began at the end of the initial third of the 15th century that was caused by late reception of the European courtesy tradition in Spain. Old translations of Infierno by Dante (Enrique de Villena, Pedro Fernández de Villegas) saw in the story of Francesca and Paolo first and foremost a cautionary example of the tragic effect of the courteous poetry and its ideals on real fates of people, thus partly determining further ways of perception of the narrative of killed lovers and its effect on the Spanish poetry and drama. The brightest expression of this idea is the episode, where Marquess de Santillana, hero of El Triumphete de Amor vision, meets the Dante’s characters and the “dona de Ravenna” gives place to Galician troubadour Macias. The national legend and didactic representation of Dante’s episode forced the narrative of Francesca and Paolo out of the Spanish literature. Lope de Vega’s play titled El castigo sin venganza written on the basis of the plot of Bandello’s novella and transformed under the influence of Dante’s episode became in a way the return to the initial and tragic essence of the story of two lovers.